2006
DOI: 10.1111/j.1538-7836.2006.01808.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and causes of death in patients with hemophilia, 1992–2001: a prospective cohort study

Abstract: Summary.  Background: Clotting factor products have been safe for HIV since 1985, and for hepatitis C since 1992. Few studies have reported on mortality in the total population of hemophilia patients after the period of risk of viral infection transmission. Objectives: We studied the mortality, causes of death, and life expectancy of hemophilia patients between 1992 and 2001. We compared these findings with those of previous cohorts, together spanning the periods before, during, and after the use of potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
323
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(341 citation statements)
references
References 22 publications
11
323
1
3
Order By: Relevance
“…[1][2][3] In this context, more and more of them are becoming confronted with a new challenge: ageing. Ageing influences their well-being, because older PWH carry the burden of the physical and psychological consequences of the inadequate treatment received in the early periods of their lives.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In this context, more and more of them are becoming confronted with a new challenge: ageing. Ageing influences their well-being, because older PWH carry the burden of the physical and psychological consequences of the inadequate treatment received in the early periods of their lives.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Furthermore, recent findings have demonstrated that prophylaxis regimens decrease bleeding, pain, the frequency and duration of hospitalizations, disability, and quality of life in the hemophiliac population. Several groups of researchers 12,13 have hypothesized that there is an obvious link between the economic capacity of a country and the availability of the coagulation factors, diagnostic facilities, patients, care levels, and death rates due to bleeding disorders. These parameters can influence the difference in the rate and type of deaths among patients with hemophilia in various countries.…”
Section: Introductionmentioning
confidence: 99%
“…They are usually associated with HCV and HIV positivity. Hepatocellular carcinoma is very important cause of death among haemophiliacs with a reported standardized mortality ratio of 17.2 (Plug, 2006) and 13.51 (Darby, 2007). Risk factors for hepatocellular carcinoma assessed in multicentre Italian study were presence of liver cirrhosis, elevated alpha fetoprotein, current HCV infection and age over 45 (Tradati, 1998).…”
Section: Malignancymentioning
confidence: 99%
“…Additionally, HIV infection and cART may per se increase the risk for metabolic and cardiovascular disease, as it was stated earlier. Indeed, it was reported recently an increasing num b e r o f d e a t h s i n haemophilia patients as a consequence of ischemic heart disease (Plug, 2006), together with increasing prevalence of ischemic heart disease among haemophilia patients 60 years of age and older (Kulkarni, 2005). Moreover, it is important to educate haemophilia patients about the cardiovascular risk factors, and on the benefit of living a healthy lifestyle ).…”
Section: Cardiovascular Disease In Elderly Patients With Hemophiliamentioning
confidence: 99%